Smartphone display size can influence perceptual judgments. (September 2021) - Sanchez, C.A.; Read, T.; Crawford, A.
Classic research in perception has suggested that visual context can impact how individuals perceive object characteristics like physical size. The current set of studies extends this work to an applied setting by examining whether smartphone display size can impact the perception of objects presented on smartphones. Participants viewed several target items, on two different sized virtual device displays based on actual consumer devices and were asked to make simple judgments of the size of presented objects. Results from both experiments confirm that display size impacts perceived size, such that larger displays cause users to significantly underestimate the size of objects moreso than smaller displays. This is the first study to confirm such an effect, and suggests that beyond aesthetics or cost, one's personal choice of device might have additional performance consequences.